2022
DOI: 10.1007/s11250-022-03048-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of somatic cell score-associated SNPs from Holstein cattle in Sudanese Butana and Butana × Holstein crossbred cattle

Abstract: The Bos indicus zebu cattle Butana is the most commonly used indigenous dairy cattle breed in Sudan. In the last years, high-yielding Holstein dairy cattle were introgressed into Butana cattle to improve their milk yield and simultaneously keep their good adaption to extreme environmental conditions. With the focus on the improvement of milk production, other problems arose such as an increased susceptibility to mastitis. Thus, genetic selection for mastitis resistance should be considered to maintain healthy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Therefore, the frequency of the T allele, which increases susceptibility to mastitis, may be shallow in Holstein cattle. Like most previous studies, it has been reported that the frequencies of alleles that are suggested to be associated with mastitis susceptibility are low in Holstein cattle [38][39][40] . Ağaoğlu et al 41 reported that TLR4 genotype frequencies associated with high milk yield and mastitis resistance are higher in Holsteins than in Turkish native cattle breeds.…”
Section: Discussionsupporting
confidence: 51%
“…Therefore, the frequency of the T allele, which increases susceptibility to mastitis, may be shallow in Holstein cattle. Like most previous studies, it has been reported that the frequencies of alleles that are suggested to be associated with mastitis susceptibility are low in Holstein cattle [38][39][40] . Ağaoğlu et al 41 reported that TLR4 genotype frequencies associated with high milk yield and mastitis resistance are higher in Holsteins than in Turkish native cattle breeds.…”
Section: Discussionsupporting
confidence: 51%
“…The somatic cell count (SCC) in milk often be used as an indirect marker for mastitis infections in the dairy breeding. An SCC of more than 100,000 cells/mL is commonly suggestive for a subclinical mastitis infection [41]. Laszlo Ozsvari et al reported that milk ELISA-positive cows had a somatic cell count that was an average of 35.8% higher than test-negative cows [42].…”
Section: Discussionmentioning
confidence: 99%